Design dialogue is a cognitive accompaniment in the designs of interior spaces(As a case study of the hospitality hall in Qasr Al Watan - Abu Dhabi (UAE) (Al-Academy, 2024)
The design dialogue is not limited to presenting old ideas that the interior designer believes in, but is based on the method of constructing the ideas that form in his mind, and this depends on clarifying the meanings generated through the presentation of the idea, as well as framing and presenting it in a scientific manner that is convincing to the other party, so that the mind remains He was aware throughout the period of the interview so that he could make a judgment about it .Thus, design dialogue represents a stylistic tool used to address one of the specialized topics, especially in a field of design science and knowledge, and even represents an aspect of design thought, and this depends on the effective role of the interior designer’s vision based on choosing the specific intellectual framework within a rational design intellectual vision. Determining the intrinsic reality of the thing to reach the design product required to be implemented and the motivating role emerging from its interaction with the place.Therefore, it was necessary to study this topic, which consists of four chapters. For the first chapter, the researcher relied on formulating the research problem, which is summarized in the following question: What are the considerations that the design dialogue adopts as a cognitive accompaniment in the designs of the interior spaces of the hospitality hall in Qasr Al Watan - Abu Dhabi (UAE)?While the importance of the research lies in achieving a communication function between the interior designer and the recipient through mental design communication that carries cognitive dimensions such that it raises in the recipient implicit dialogue meanings that are capable of sensory perception. In light of this, the researcher focused the research goal on arriving at knowledge of the most important considerations adopted by design dialogue. As a knowledge update in the designs of the interior spaces of the hospitality hall in Qasr Al Watan - Abu Dhabi (UAE)،As for the limits of the research, the researcher has defined, in terms of the objective limit, “design dialogue, keeping pace with knowledge in the designs of interior spaces” as a case study of the hospitality hall in Qasr Al Watan - Abu Dhabi (UAE), while its spatial and temporal boundaries include the modern interior spaces, represented by the hospitality hall in Qasr Al Watan. Al Watan - Abu Dhabi (UAE) implemented in 2019 AD,While the second chapter was based on studying, firstly: considerations of design dialogue, and secondly, considerations of cognitive accompaniment, while the third chapter included defining the subject of the research procedures, represented by the research methodology based on the descriptive and analytical approach, while the research community focused on adopting the intentional selective method, and finally, the fourth chapter included drawing the results of the research.